Central bank independence: Myth and misunderstanding - L. Randall Wray (Levy Economics Institute of Bard College, 2014)
It is commonplace to speak of central bank "independence" as if it were both a reality and a necessity. While the Federal Reserve is subject to the "dual mandate", it has substantial discretion in its interpretation of the vague call for high employment and low inflation. Most important, the Fed's independence is supposed to insulate it from political pressures coming from Congress and the US Treasury to "print money" to finance budget deficits. As in many developed nations, this prohibition was written into US law from the founding of the Fed in 1913. In practice, the prohibition is easy to evade, as we found during World War II, when budget deficits ran up to a quarter of US GDP. If a central bank stands ready to buy government bonds in the secondary market to peg an interest rate, then private banks will buy bonds in the new-issue market and sell them to the central bank at a virtually guaranteed price. Since central bank purchases of securities supply the reserves needed by banks to buy government debt, a virtuous circle is created, so that the treasury faces no financing constraint. That is what the 1951 Accord was supposedly all about: ending the cheap source of US Treasury finance. Since the global financial crisis hit in 2007, these matters have come to the fore in both the United States and the European Monetary Union, with those worried about inflation warning that the central banks are essentially "printing money" to keep sovereign-government borrowing costs low. ...
Keywords: E5; E58; E63; N2; N22; 330; Central Bank Independence; 1951 Accord; Fed Independence; Fed Transparency; Fed Governance; Accountability of the Fed; Dodd-Frank; Federal Reserve Act; Dual Mandates; Central Bank Discretion; Modern Money Theory; State Money